What is the importance of vaccine hesitancy in the drop of vaccination coverage in Brazil? - Sato, Ana Paula Sayuri (Revista de saúde pública, 2018)
The successful Programa Nacional de Imunizações do Brasil (Brazilian National Immunization Program) has been experiencing a major challenge with regard to vaccination coverage for children, which has been dropping. Several aspects are related, but certainly vaccine hesitancy has been strengthening itself as one of the main concerns of Brazilian public administrators and researchers. Vaccine hesitancy is the delay in acceptance or refusal despite having the recommended vaccines available in health services, being a phenomenon that varies over time, over location and over types of vaccines. Hesitant individuals are between the two poles of total acceptance and refusal of vaccination. Vaccine hesitancy is nothing new in European and North-American countries, and even in Brazil, it has been studied even if under another name. The drop of vaccination coverage observed from 2016 on reiterates the relevance of the theme, which must be better understood through scientific research.